Unmanned Aerial Vehicle (UAV) Technology Use in Visual Road Inspection at Ft005, Johor Bahru-Melaka (Pengkalan Raja, Pontian) - Basri, Nor Athirah; AHMAD TAJUDIN, SAIFUL AZHAR (Recent Trends in Civil Engineering and Built Environment, 2022)
Visual road inspection is one of the key phases of road maintenance, but local authority still uses conventional road inspection method, that is the manual walking survey method, to collect data on pavement distresses. However, this method has its drawbacks, as the data obtained is less accurate due to some constraints that arise and the costs rose as it required many employees to conduct these surveys. Therefore, the purpose of this study is to determine the extent to which alternative methods using UAV technology can help in the development of a road distress data in pavement distresses information search and determining the severity level of road in visual road inspection. This study’s processes included preliminary planning, capturing images using UAV technology, producing orthomosaic and Digital Surface Model (DSM) images with Pix4DMapper software, analysis the images with Global Mapper software to determine location and type of pavement distress, and finally determining severity level of road with the Pavement Condition Index (PCI) method. As a result of this study, the pavement distress of this road from section 1 to 4 is at a serious level and necessitates reconstruction.